Reversible Computation 7th International Conference, RC 2015, Grenoble, France, July 16-17, 2015, Proceedings - Krivine, Jean.; Stefani, Jean-Bernard.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 7th International Conference on Reversible Computation, RC 2015, held in Grenoble, France in July 2015. The 19 papers presented together with 1 invited talk were carefully reviewed and selected from 30 submissions. The Conference on Reversible Computation particularly includes the following topics: reversible machines, reversible languages, design and verification of quantum circuits, design of reversible circuits, and circuit synthesis.
Invited Paper -- Moment Semantics for Reversible Rule-Based Systems -- Reversible machines -- A Hierarchy of Fast Reversible Turing Machines -- Real-time methods in reversible computation -- Reversible Ordered Restarting Automata -- Reversible Languages -- Garbage Collection for Reversible Functional Languages -- Reverse Code Generation for Parallel Discrete Event Simulation -- Towards a Domain-Specific Language for Reversible Assembly Sequences -- Design and verification of quantum circuits -- Reversibility in Extended Measurement-based Quantum Computation -- A Fully Fault-Tolerant Representation of Quantum Circuits -- Equational reasoning about quantum protocols -- Design of reversible circuits -- Design and Fabrication of a Microprocessor using Adiabatic CMOS and Bennett Clocking -- Improved Algorithms for Debugging Problems on Erroneous Reversible Circuits -- Ricercar: A Language for Describing and Rewriting Reversible Circuits with Ancillae and its Permutation Semantics -- Circuit Synthesis -- Technology Mapping for Single Target Gate based Circuits using Boolean Functional Decomposition -- Towards Code Optimization for Line-aware HDL-based Synthesis of Reversible Circuits -- Synthesis of Quantum Circuits for Dedicated Physical Machine Descriptions -- Short Papers -- Power-Clock Generator Impact on the Performance of NEM-Based Adiabatic Logic Circuits -- A Cost Metric for the Design of Nearest Neighbor Quantum Circuits at the Reversible Logic Level -- Towards modelling of local reversibility -- Application of Functional Decomposition in Synthesis of Reversible Circuits.
Keywords: Computer science; Logic design; Software engineering; Computers; Algorithms; Computer logic; Quantum computers; Computer Science; Logic Design; Logics and Meanings of Programs; Quantum Computing; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Software Engineering; Electronic books